Fall survival of American woodcock in the western Great Lakes Region. Issue 5 (8th April 2013) - Bruggink, John G.; Oppelt, Eileen J.; Doherty, Kevin E.; Andersen, David E.; Meunier, Jed; Lutz, R. Scott
Abstract We estimated fall (10 Sep–8 Nov) survival rates, cause‐specific mortality rates, and determined the magnitude and sources of mortality of 1, 035 radio‐marked American woodcock (Scolopax minor) in Michigan, Minnesota, and Wisconsin during 2001–2004. In all 3 states, we radio‐marked woodcock on paired study areas; 1 of which was open to hunting and expected to receive moderate to high hunter use and the other of which was either closed to hunting (Michigan and Minnesota) or was relatively inaccessible to hunters (Wisconsin). We used Program MARK to estimate fall survival rates, to evaluate a set of candidate models to examine the effects of hunting and several covariates (sex, age, year, state) on survival, and to examine the relationship between survival rates and kill rates due to hunting. Hunting accounted for 70% of the 86 woodcock deaths in the hunted areas, followed by predation (20%) and various other sources of mortality (10%). Woodcock deaths that occurred in the non‐hunted and lightly hunted areas (n = 50) were caused by predators (46%), hunting (32%), and various other sources (22%). Based on small‐sample corrected Akaike's Information Criterion values, variation in fall survival of woodcock was best explained by treatment (i.e., hunted vs. non‐hunted), year, and period (pre‐hunting season intervals vs. hunting season intervals). The average fall survival estimate from our best model for woodcock in the non‐hunted areas (0.893, 95% CI = 0.864–0.923) was greater than the average for the hunted areas (0.820, 95% CI = 0.786–0.854 [this estimate includes data from the lightly hunted area in Wisconsin]), and the average treatment effect (i.e., greater survival rates in non‐hunted areas) was 0.074 (95% CI = 0.018–0.129). The kill rate due to hunting was 0.120 (95% CI = 0.090–0.151) when data were pooled among states and years. We detected a negative relationship between hunting kill rates and survival in our hunted areas, which suggests that hunting mortality was at least partially additive during fall. Our results illustrate the influence of hunting relative to other sources of mortality in Michigan, Minnesota, and Wisconsin, and indicate that managers may be able to influence fall survival rates by manipulating hunting regulations or access on public land. © 2013 The Wildlife Society.